Diversified crop rotations enhance yield stability but require strategic grain storage for profitability in southern Brazil - Tiago Santos Telles; Gabriel Eiji Higashi; Bruno Volsi; Ivan Bordin; Adonis Moreira (Journal of Agriculture and Food Research, 2025)
Crop rotation with species diversification allows to increase yield, however, there is few information on the profitability of this practice. This study aimed to determine whether crop rotation systems are more productive and economically advantageous than double-cropping rotations without diversification in subtropical conditions. The experiment was conducted in a typical Oxisol of the Caiuá sandstone area, southern Brazil, from the agricultural year 2014–2015 to 2019–2020. The experimental design was randomized blocks, with five treatments and four blocks. The treatments consisted of four crop rotations with different levels of species diversification compared to control treatment with Brachiaria-soybean rotation, all of which were managed under no-till. Yield, revenue, total cost, and profit were considered to determine the profitability of the agricultural systems. All agricultural systems resulted economic losses, probably due to occurrences of the ‘El Niño-Southern Oscillation’. Inputs represented approximately 60 % of the total cost, mainly due to expenses of fertilizers. In the soils of the Caiuá sandstone area, fertilizer costs—which represent an average of 25 % of the total cost—compromise the profitability of agricultural systems. Considering the possibility of the grain storage and future sale of corn and soybean at periods with better price, most of the evaluated agricultural systems could show economic profit, mainly in more diversified crop rotations systems. While all systems showed economic losses due to El Nino-Southern Oscillation (ENSO) and high fertilizer costs, strategic grain storage and delayed sales could reverse losses, particularly in diversified rotations.